2023
DOI: 10.1177/23259671221144786
|View full text |Cite
|
Sign up to set email alerts
|

Closing-Wedge Posterior Tibial Slope–Reducing Osteotomy in Complex Revision ACL Reconstruction

Abstract: Background: A posterior tibial slope (PTS) >12° has been shown to correlate with failure of anterior cruciate ligament (ACL) reconstruction (ACLR). PTS-reducing osteotomy has been described to correct the PTS in patients with a deficient ACL, mostly after failure of primary ACLR. Purpose: To report radiologic indices, clinical outcomes, and postoperative complications after PTS-reducing osteotomy performed concurrently with revision ACLR (R-ACLR). Study Design: Case series; Level of evidence, 4. Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…6 More recently, proximal tibial osteotomies have been indicated in patients with a PTS .12°to decrease the risk of ACL graft failure, especially in the revision setting. 3,11,12,37,40,41 In our study of patients who underwent combined ACL and PCL reconstruction, no differences were seen for PROs, Lachman test, ACL graft failure, or ACL revision in patients with a PTS .12°.…”
Section: Discussionmentioning
confidence: 54%
“…6 More recently, proximal tibial osteotomies have been indicated in patients with a PTS .12°to decrease the risk of ACL graft failure, especially in the revision setting. 3,11,12,37,40,41 In our study of patients who underwent combined ACL and PCL reconstruction, no differences were seen for PROs, Lachman test, ACL graft failure, or ACL revision in patients with a PTS .12°.…”
Section: Discussionmentioning
confidence: 54%
“… 8 In revision ACLR with a high tibial slope, TDO can reduce the SATT. The SATT was reduced from 8.5 to 3.6 mm in the setting of primary and secondary revision ACLR when combined with a TDO 53 and from 11.7 ± 5.2 mm to 4.3 ± 2.5 mm in secondary revision ACLR when combined with a TDO, 10 and a small number of cases demonstrated increased tibial slope and SATT in the primary TDO and ACLR setting. 6 The present study reports an important negative finding—LET did not influence SATT.…”
Section: Discussionmentioning
confidence: 86%
“…Biomechanical studies have demonstrated that decreasing PTS by high tibial osteotomy has a protective effect on ACL grafts by reducing the load applied on the graft 28,29 . Clinical implementation of this concept shows promising results [30][31][32] . However, osteotomies are significant procedures with elevated complication rates.…”
Section: Discussionmentioning
confidence: 95%